Brief reflections on judgments in the process of Peruvian labor reform - Laiza Espinoza, Gloria Lucila (2022)
Topics of legal argumentation in labor judgments, under Act No. 29497, New Labor Procedural Act, contain some questions and reflections of some aspects that, in our opinion, have not been addressed with the necessary seriousness and relevance, such as labor court judgments, specifically, in the precision and accurateness degrees that involve its argumentation, since the judgment contains certain guidelines which differentiate it from sentences issued within the framework of other judicial proceedings, such as criminal, civil, family proceedings, etc. In this sense, this article provides some constructive criticism and attempted elements of judgment, in order to novate it in the circuit of issuing of sentences in said Act, emphasizing on argumentation.